The Effect of Social Media Promotion Content Quality and Consumer Confidence Levels on Purchasing Interest: A Case Study on Tiktok Shop - Maria Ratnoya Nunu; Siti Masruroh (JIBEMA: Jurnal Ilmu Bisnis, Ekonomi, Manajemen, dan Akuntansi, 2026)
This research aims to analyze the influence of the quality of social media promotional content and the level of consumer trust in buying interest in TikTok Shop. The research used a quantitative approach using a survey method of 100 respondents. The data analysis techniques used include validity, reliability tests, classical assumption tests, multiple linear regression analysis, t tests, F tests, and coefficient of determination (R²) with the help of the SPSS program. The results showed that the quality of social media promotional content had a positive and significant effect on buying interest with a regression coefficient of 0.717 and a significance. The level of consumer confidence also positively and significantly influences purchasing interest with a regression coefficient of 0.455 and a significance. Simultaneously, both variables had a significant influence on purchasing interest with a determination coefficient (R²) value of 0.846, which means they were able to explain the influence of 84.6%, while 15.4% was influenced by other factors outside the study. Based on the research results, it can be concluded that the better the quality of social media promotional content and the higher the level of consumer trust, the increased buying interest in TikTok Shop will increase.